Development of SIGA-ME: A management tool for evaluating costs, waste, and water footprint in school meals in Presidente Bernardes-SP - Uliana, Maíra Rodrigues; Lima, Marcus Ayrton Rocha de; Mafra, Renata Cristina; Costa, Sérgio Marques; Arana, Alba Regina Azevedo (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
For administration, indicators function like a compass in navigation. Based on their availability, quantity, and quality, decision-makers are better assisted in their daily tasks. In public administration, it is no different; however, it is very common for small municipalities, such as Presidente Bernardes-SP, to require managerial support to aid in this task. The aim of the article was to develop a database tool for generating cost and waste indicators in school meals for elementary school students, as well as to calculate and identify the virtual water used in food preparation. Thus, this work was developed through the construction of a system designed in Microsoft Access. The approach employed to achieve this goal was applied research. Consequently, the SIGA-ME system—Applied Management Information System—School Meals was created. The result was the provision of a duly parameterized tool for the municipality. The database includes stock movement entries for twenty days in March 2020. The researcher registered the application with the National Institute of Industrial Property (INPI).